2022
DOI: 10.3390/ijerph19031297
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Oral Cancerous and Precancerous Lesions in an Underserved Community: A Cross-Sectional Study

Abstract: Street-involved people with limited access to regular healthcare have an increased risk of developing oral cancer and a lower survival rate. The objective of this study was to measure the prevalence of oral cancerous/precancerous lesions and determine their associated risk factors in a high-risk, underserved population. In this cross-sectional study, English-speaking adults aged 18 years and older living in a marginalized community in Edmonton were recruited from four non-profit charitable organizations. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Indeed, modeling evidence has suggested that screening US men aged 50 to 70 years who are smokers has reasonable efficiency. 52 In the community setting, however, proof-of-concept programs in the US, [53][54][55] Canada, 56 and the UK 57 have demonstrated low yields and high false-positive cases; this might mean that existing criteria for identifying high-risk populations should be expanded. For instance, in Ontario, Canada, which is ethnically diverse, incidence rates for OC among first-and secondgeneration South and Southeast Asian groups are just as high as those in South and Southeast Asia, where successful screening programs exist.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, modeling evidence has suggested that screening US men aged 50 to 70 years who are smokers has reasonable efficiency. 52 In the community setting, however, proof-of-concept programs in the US, [53][54][55] Canada, 56 and the UK 57 have demonstrated low yields and high false-positive cases; this might mean that existing criteria for identifying high-risk populations should be expanded. For instance, in Ontario, Canada, which is ethnically diverse, incidence rates for OC among first-and secondgeneration South and Southeast Asian groups are just as high as those in South and Southeast Asia, where successful screening programs exist.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, proper support and care of aged individuals will help the dentist in proper diagnosis and treatment planning programs. 5…”
Section: Success In the Specialty Of Oral Medicinementioning
confidence: 99%